Accelerating the Passage to Citizenship: Marriage and Naturalization in France - McAvay, Haley; Waldinger, Roger (Frontiers in Sociology, 2021)
Naturalization systems often provide immigrant spouses of citizens with accelerated access to citizenship, but thus far, the impact of such fast-track procedures has yet to be examined by empirical analysis. Towards that end, we leverage a unique feature of French naturalization policy: a dual track system, one for standard naturalization and a second that makes naturalization a right for non-citizens married to citizens. We show that, overall, family-level factors exercise the greatest influence on naturalization decisions relative to individual and contextual factors; further, marriage to French citizens is the single most powerful factor, yielding effects on naturalization in both tracks. However, while marriage to a naturalized citizen promotes standard naturalization, marriage to a French native fosters citizenship via the marriage track. Women migrants who marry French natives are particularly likely to naturalize via marriage. Contributing to the study of naturalization by attending to the link between two institutions – naturalization and marriage – we show that the effects of an apparent bias towards the familial ties of citizens run up against state efforts to close off membership to outsiders.